Pengaruh Health Coaching Berbasis Teori Health Belief Model Terhadap Tekanan Darah Pada Lansia Dengan Hipertensi - Hastuti, Apriyani Puji; Mufarokhah, Hanim (Journal of Islamic Medicine, 2019)
Introduction: Most people with hypertension assume that consumption drugs can control their blood pressure. In fact, lifestyle factor such as physical activity contribute to the burden of account for substantial morbidity, mortality, and rising in hypertension, highlighly the much for prevention afford to curb public health epidemic. Health coaching was one way for the nurse to improve motivation and patient’s beliefs concerning their disease so that they would show good compliance behavior. Objective of this study was to analyze the effect of health coaching toward physical activity. Methods: This study used quasi experiment design with pre-post test control group design. Sample collection technique was by purposive sampling. The amount of sample was 26 person for each group. There were two variables, the dependent and independent variables, the dependent variable was physical activity and the independent variable was health coaching. The location in the work Pandanwangi health public care and the time was April- Juli 2019. Statistical data test used were Mann Whitney and Sign Rank Test Wilcoxon. Result: Health coaching has effect to systolic blood pressure only. Difference test in treatment group using Wilcoxon obtain p value 0,000, while differece test with Mann Whitney obtain p value 0,000 . Discussion : There is blood pressure differences between treatment and control group. It is expected hypertension patients should be always doing use hypertension management to control blood pressure. Keywords: health coaching, hypertension, blood pressure